Activity of ethanolic extract of Eucalyptus globulus leaves against multi drug resistant poultry pathogens in broiler chicks - Ullah, Assad; Anjum, Aftab Ahmad; Rabbani, Masood; Ijaz, Muhammad; Nawaz, Muhammad; Ashraf, Muhammad; Ali, Asad; Rashid, Anjum; Najeeb, Imran; Hussain, Ahmad (Cellular and Molecular Biology, 2021)
The present study was designed to evaluate the antimicrobial activity of E. globulus leaves in broiler chicks. Total (n=255) day-old chicks were segregated into five groups i.e. Pathogenic E. coli, S. pullorum, S. gallinarum and C. perfringens type A and control negative group. Each bacterial challenged (1x 107 CFU) group was divided into control positive, antibiotic, probiotic and E. globulus group. Experimental birds were exposed to E. coli, S. pullorum, S. gallinarum and C. perfringens type A at different ages. At 35th day of experiment the log reduction for each group was determined. The highest log reduction in E. coli and C. perfringens Type A colonies count were found in E. globulus (3.26) (2.33) treated group followed by antibiotic (2.85) (1.59) and probiotic (2.84) (1.50) respectively. The log reduction in S. pullorum colonies count was highest in E. globulus (2.50) followed by probiotic (2.24) and antibiotic (2.16). The S. gallinarum colonies count log reduction was found highest for antibiotic (2.84) followed by probiotic (2.48) and E. globulus group. The results of in-vivo experiment revealed that ethanolic extract of E. globulus has antibacterial activity and it can be used as a replacement to low level of antibiotics added in poultry feed.